High temperature oxidation of mechanically alloyed NiAl-Fe-AlN-Al2O3 - Lee, DB; Kim, GY; Park, SW; Ur, SC (ELSEVIER SCIENCE SA, 2002)
A new NiAl-Fe alloy containing uniformly distributed ultra-fine AlN and Al2O3 dispersoids was produced by mechanical alloying in a controlled atmosphere and by subsequent hot extrusion process. The new NiAl-Fe-AlN-Al2O3 alloy was oxidized in the temperature range between 1073 and 1473 K in air. The alloy displayed similar oxidation behavior with conventional NiAl alloys. As the oxidation temperature increased, the oxidation rate, the scale thickness and scale spallation increased. The scales formed during isothermal and cyclic oxidation consisted primarily of alpha-Al2O3. No transient, metastable aluminas were found. The presence of not nitrogen but iron and nickel within the alumina scales was observed. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: DUCTILITY; SCALES; FE